How can a municipality support companies' investment decision? :case Rajakangas - Keloneva, Elina (2022)
Keminmaa is a region in Sea-Lapland, between two bigger industrial cities, Kemi and Tornio, and an ideal location for business direct either way. The objective of this applied business research was to form an understanding of the relevant issues that support decision-making processes related to investments. The aim was to find out whether Keminmaa municipality could make Rajakangas business area more enticing for companies to start investing in Keminmaa. The theoretical framework of the study was formed by familiarizing with literature considering company decision-making and municipality activities. The background study included familiarization with town and region planning in Northern Finland and especially in Keminmaa. To understand the bigger picture of decision- making the importance of information and its proper usage had to be examined. The thesis research was carried out as a case study. Data was collected with interviews with selected target group formed of business executives and municipal official. The goal was to get specific information considering Rajakangas business area and its possibilities. Data from prior electronic survey considering communication between municipality and companies was analyzed to understand the preferable operational models between parties. The results of the study indicate that by operating openly and cooperatively with companies a municipality can fortify the positive operational environment, hence be more an attractive location to companies. The role of municipality, as the most important areal policy holder, highlights the meaning of business atmosphere, when examining the interface between administration and companies. Based on the received answers companies agreed that the location of Rajakangas is excellent and future development possibilities are interesting. Nevertheless, during the writing of this thesis, companies struggle with great uncertainty considering the current global situation with Covid-19 and Russian invasion of Ukraine. Those have increased expenses and ...